Industrial wastewater treatment, recycling and reuse - Ranade, Vivek V. (Butterworth-Heinemann, 2014)
Industrial Wastewater Treatment, Recycling and Reuse is an accessible reference to assist you when handling wastewater treatment and recycling. It features an instructive compilation of methodologies, including advanced physico-chemical methods and biological methods of treatment. It focuses on recent industry practices and preferences, along with newer methodologies for energy generation through waste. The book is based on a workshop run by the Indus MAGIC program of CSIR, India.